A qualitative analysis of health service problems and the strategies used to manage them in the COVID-19 pandemic: exploiting generic and context-specific approaches - Hania Rahimi-Ardabili; Farah Magrabi; Brenton Sanderson; Thilo Schuler; Enrico Coiera (BMC, 2024)
Abstract Background The COVID-19 pandemic disrupted health systems around the globe. Lessons from health systems responses to these challenges may help design effective and sustainable health system responses for future challenges. This study aimed to 1/ identify the broad types of health system challenges faced during the pandemic and 2/ develop a typology of health system response to these challenges. Methods Semi-structured one-on-one online interviews explored the experience of 19 health professionals during COVID-19 in a large state health system in Australia. Data were analysed using constant comparative analysis utilising a sociotechnical system lens. Results Participants described four overarching challenges: 1/ System overload, 2/ Barriers to decision-making, 3/ Education or training gaps, and 4/ Limitations of existing services. The limited time often available to respond meant that specific and well-designed strategies were often not possible, and more generic strategies that relied on the workforce to modify solutions and repair unexpected gaps were common. For example, generic responses to system overload included working longer hours, whilst specific strategies utilised pre-existing technical resources (e.g. converting non-emergency wards into COVID-19 wards). Conclusion During the pandemic, it was often not possible to rely on mature strategies to frame responses, and more generic, emergent approaches were commonly required when urgent responses were needed. The degree to which specific strategies were ready-to-hand appeared to dictate how much a strategy relied on such generic approaches. The workforce played a pivotal role in enabling emergent responses that required dealing with uncertainties.